Semiotic of Heartbreak: A Roland Barthes Analysis of Luka Dalam Lyrics by Manja Mooy - Aran, Maria Trifonia Teniba; Setyowati, Endang; Muliyono , Nurwakhid (UIBU, 2026)
This study analyzes the meaning of the lyrics of Manja Mooy's song